2010
DOI: 10.1177/1934578x1000500235
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activities of Ocimum sanctum Essential Oil and its Lead Molecules

Abstract: Aqueous extracts and oils of five Indian medicinal plants, traditionally used for their antimicrobial activities, were evaluated against two of the most prevalent Candida species causing candidiasis, C. albicans and C. tropicalis. Of these plant materials, three showed varying degrees of antifungal activity against both species. Tulsi (Ocimum sanctum Linn.) essential oil (TEO) was found to be the most effective, followed by Peppermint essential oil, and Aloe vera aqueous leaf extract. The product with the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 19 publications
0
51
0
4
Order By: Relevance
“…It is known that conventional antifugal treatments have limitations associated with their toxicity, antifungal resistance, relapses and high treatment costs (Khan et al . ). The presence of clinical isolates of terbinafine‐resistant T. rubrum exhibiting high‐level primary resistance to terbinafine, which is one of the most used antifungal drugs (Mukherjee et al .…”
Section: Resultsmentioning
confidence: 97%
“…It is known that conventional antifugal treatments have limitations associated with their toxicity, antifungal resistance, relapses and high treatment costs (Khan et al . ). The presence of clinical isolates of terbinafine‐resistant T. rubrum exhibiting high‐level primary resistance to terbinafine, which is one of the most used antifungal drugs (Mukherjee et al .…”
Section: Resultsmentioning
confidence: 97%
“…In this study MIC of L. alba was 312 μg/mL against M. gypseum , higher value than that found in our study. The antifungal activity of Ocimum sanctum essential oil (and its major components) including linalool against Candida albicans , and results were found by Cardoso et al., in which Ocimum basilicum essential oil and linalool also inhibited C. albicans . Linalool has also shown antifungal activity against Cryptococcus neoformans by reducing its capsule size .…”
Section: Discussionmentioning
confidence: 90%
“…The plasma membrane plays a vital role in maintaining a homeostatic environment to keep cells healthy and maintain fungal cell viability. Studies have shown that linalool interacts with fungal cell membranes by disrupting ergosterol biosynthesis in Candida albicans . In fact, ergosterol is an important structural component of fungal cell membranes for maintenance of the cell membrane structure and fluidity.…”
Section: Discussionmentioning
confidence: 99%
“…The ethanolic extract of L. aspera root showed a significant free-radical scavenging activity and lethality to brine shrimp (Rahman et al 2007). Linalool was the most active constituent isolated from the essential oil of O. sanctum used for their antimicrobial activities against Candida albicans and Candida tropicalis (Khan et al 2010). The compounds, ferulaldehyde, ulsoric acid, tulsinol C, Eugenol dimers 11 and 12 isolated from the leaf methanol extract of O. sanctum showed strong leishmanicidal activity against promastigotes of Leishmania major (Suzuki et al 2009).…”
Section: Resultsmentioning
confidence: 99%